Educación médica: Nuevas tendencias, desafíos y opor tunidades - Risco de Dominguez, Graciela (2015)
In this context 'competencybased education' is considered the predominant educational  model for Medicine Faculties in the world and is the revolutionary medical education concept for the 21st century.The new doctors should have competencies such as: basic clinical skills, patient  management, public health, having scientific grounds of medicine and the investigation and application of scientific methods. The development of these competencies requires  a new educational methodology. In Peru it is important to take into account this criteria  so that we can create doctors who are capable of resolving the critical health situation of our country. This commitment has inspired the creation of the Faculty of Medicine of Universidad Peruana de Ciencias Aplicadas (UPC)